Konflik Hukum dalam Tata Negara Indonesia Terkait Penarikan Kewarganegaraan : Perspektif Konstitusional - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Intan Marhenisaputri; Aulia Azizah P Pure (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study explains the effect of changes in citizenship on land tenure rights in agrarian law. Using qualitative analysis and interviews, the research found that changes in citizenship status often lead to shifts in land ownership rights. Current agrarian law is considered not fully responsive to these dynamics, so reform is needed to face the challenges of globalization and international mobility.